DISCOURSE DEIXIS OF SUHO EXO’S SPEECH AT THE STANFORD KOREA PROGRAM’S 20TH ANNIVERSARY CONFERENCE - Reziana, Salsabila Rosya; Sariyati, Ice; Budiarti, Dian (CALL, 2024)
Deixis is an essential component of communication that must be carefully considered to improve its efficiency and prevent misunderstandings. This study aimed to analyze Suho EXO’s speech at the Stanford Korea Program 20th Anniversary Conference focused on the discourse deixis and types of discourse deixis used and investigate their functions. The research employed a qualitative method. A theory used in this study was based on the Levinson’s deixis theory (1983). Discourse deixis refers to deictic references to segments of discourse relative to the speaker’s current position within the discourse. Discourse deixis, like anaphora and cataphora, can serve as a cohesive device within a text. The analysis found 53 deictic expressions in 38 utterances in the speech. The types of discourse deixis found in the speech were it (20 data), this (10 data), and (7 data), these (4 data), but (4 data), that (2 data), so (2 data), those (1 datum), there (1 datum), or (1 datum), and actually (1 datum). Moreover, 34 data contained anaphora functions, such as and, it, this. Meanwhile, 19 data contained cataphora functions, such as that, but, or, so, these, those, and actually. Therefore, paying attention to deixis leads to more distinctive, accurate, and compelling conversations.Keyword: discourse deixis, speech, suho EXO